Preliminary design and analysis of a novel solar receiver for a micro gas-turbine based solar dish system. (April 2015) - Aichmayer, Lukas; Spelling, James; Laumert, Björn
Highlights: Detailed numerical model of volumetric solar receiver established. Multi-objective optimization used to examine design trade-offs. Pressurized and volumetric receiver designs evaluated and compared. Prototype pressurized volumetric receiver developed. Abstract: The solar receiver is one of the key components of hybrid solar micro gas-turbine systems, which would seem to present a number of advantages when compared with Stirling engine based systems and photovoltaic panels. In this study a solar receiver meeting the specific requirements for integration into a small-scale (10 kWel ) dish-mounted hybrid solar micro gas-turbine system has been designed with a special focus on the trade-offs between efficiency, pressure drop, material utilization and economic design. A situation analysis, performed using a multi-objective optimizer, has shown that a pressurized configuration, where the solar receiver is placed before the turbine, is superior to an atmospheric configuration with the solar receiver placed after the turbine. Based on these initial design results, coupled CFD/FEM simulations have been performed, allowing detailed analysis of the designs under the expected operating conditions. The results show that the use of volumetric solar receivers to provide heat input to micro gas-turbine based solar dish systems appears to be a promising solution; with material temperatures and material stresses well below permissible limits.